Proteomic analysis of radiation-induced changes in rat lung: modulation by the superoxide dismutase mimetic MnTE-2-PyP5+ - Yakovlev, Vasily A.; Rabender, Christopher S.; Sankala, Heidi; Gauter-Fleckenstein, Benjamin; Fleckenstein, Katharina; Batinic-Haberle, Ines; Jackson, Isabel; Vujaskovic, Zeljko; Anscher, Mitchell S.; Mikkelsen, Ross B.; Graves, Paul R. (International journal of radiation oncology, biology, physics, 2010)
Purpose - To identify temporal changes in protein expression in the irradiated rat lung and generate putative mechanisms underlying the radioprotective effect of the manganese superoxide dismutase mimetic MnTE-2-PyP5+. - Methods and Materials - Female Fischer 344 rats were irradiated to the right hemithorax with a single dose of 28 Gy and killed from day 1 to 20 weeks after irradiation. Proteomic profiling was performed to identify proteins that underwent significant changes in abundance. Some irradiated rats were administered MnTE-2-PyP5+ and changes in protein expression and phosphorylation determined at 6 weeks after irradiation. - Results - Radiation induced a biphasic stress response in the lung, as shown by the induction of heme oxygenase 1 at 1-3 days and at 6-8 weeks after irradiation. At 6-8 weeks after irradiation, the down-regulation of proteins involved in cytoskeletal architecture (filamin A and talin), antioxidant defense (biliverdin reductase and peroxiredoxin II), and cell signaling (β-catenin, annexin II, and Rho-guanosine diphosphate dissociation inhibitor) was observed. Treatment with MnTE-2-PyP5+ partially prevented the apparent degradation of filamin and talin, reduced the level of cleaved caspases 3 and 9, and promoted Akt phosphorylation as well as β-catenin expression. - Conclusion - A significant down-regulation of proteins and an increase in protein markers of apoptosis were observed at the onset of lung injury in the irradiated rat lung. Treatment with MnTE-2-PyP5+, which has been demonstrated to reduce lung injury from radiation, reduced apparent protein degradation and apoptosis indicators, suggesting that preservation of lung structural integrity and prevention of cell loss may underlie the radioprotective effect of this compound.